DIMINUTION AND OVERSTATEMENT IN STYLISTIC DEVICES - Bozorova Dilafza Ikrom qizi (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract: In the article diminution and increase of sense, size and various qualities in some stylistic devices are explored. In the article it is noted that meiosis, litotes, euphemism, anticlimax have the functions of reduction but hyperbole, vulgarism, sarcasm, climax have the functions of increase. Besides, examples have been taken for fusions of some stylistic devices.